Pattern of Seed Germination in Different Accessions of Calophyllum inophyllum L. in South Gujarat - Sreekumar, Rahul; Gunaga, R P (Cannarium, 2020)
The main objective of the present study is to assess seed germination performance of C. inophyllum in south Gujarat condition. Therefore, seeds were collected from different seed sources of Karnataka and Maharashtra and a preliminary study was carried out in the College of Forestry, ACHF, Navsari Agricultural University during 2015. Seeds were collected from 15 trees (good bearing) representing five populations of Maharashtra and Karnataka, and assessed for seed parameters and germination. Seed kernels were used for germination trials. Germination started from 10 to 20 days after sowing and completed maximum germination within 20-25 days after sowing. Seeds collected from CIMV1, CIMV2 and CIMN3 accessions resulted in early germination. The overall result showed that seed germination among 15 accessions ranged between 40% (CIMP4) to 100% (CIKK1; CIKK2). Considering each seed source, the seed germination was found to be highest in the seeds collected from Kumta, Karnataka. Tree to tree variation within a seed source for germination was also recorded and ranges of germination within each seed source are as follows: Dapoli (73.33-90%), Navare (60-93.33%), Purnagharh (40-93.33%), Vettye (93.33-96.67%) and Kumta (63.33-100%). In conclusion, the seed germination of C. inophyllum under south Gujarat condition showed a positive performance. This study may help for further assessment of seedlings at field condition of this region.The main objective of the present study is to assess seed germination performance of C. inophyllum in south Gujarat condition. Therefore, seeds were collected from different seed sources of Karnataka and Maharashtra and a preliminary study was carried out in the College of Forestry, ACHF, Navsari Agricultural University during 2015. Seeds were collected from 15 trees (good bearing) representing five populations of Maharashtra and Karnataka, and assessed for seed parameters and germination. Seed kernels were used for germination trials. Germination started from 10 to 20 days after sowing and completed maximum germination within 20-25 days after sowing. Seeds collected from CIMV1, CIMV2 and CIMN3 accessions resulted in early germination. The overall result showed that seed germination among 15 accessions ranged between 40% (CIMP4) to 100% (CIKK1; CIKK2). Considering each seed source, the seed germination was found to be highest in the seeds collected from Kumta, Karnataka. Tree to tree variation within a seed source for germination was also recorded and ranges of germination within each seed source are as follows: Dapoli (73.33-90%), Navare (60-93.33%), Purnagharh (40-93.33%), Vettye (93.33-96.67%) and Kumta (63.33-100%). In conclusion, the seed germination of C. inophyllum under south Gujarat condition showed a positive performance. This study may help for further assessment of seedlings at field condition of this region.